Body size predicts ontogenetic nitrogen stable-isotope (δ15N) variation, but has little relationship with trophic level in ectotherm vertebrate predators - Villamarín, Francisco; Jardine, Timothy D.; Bunn, Stuart E.; Malvasio, Adriana; Piña, Carlos Ignacio; Jacobi, Cristina Mariana; Araújo, Diogo Dutra; de Brito, Elizângela Silva; de Moraes Carvalho, Felipe; da Costa, Igor David; Verdade, Luciano Martins; Lara, Neliton; et al. (Scientific reports, 2024)
Large predators have disproportionate effects on their underlying food webs. Thus, appropriately assigning trophic positions has important conservation implications both for the predators themselves and for their prey. Large-bodied predators are often referred to as apex predators, implying that they are many trophic levels above primary producers. However, theoretical considerations predict both higher and lower trophic position with increasing body size. Nitrogen stable isotope values ( δ 15 N) are increasingly replacing stomach contents or behavioral observations to assess trophic position and it is often assumed that ontogenetic dietary shifts result in higher trophic positions. Intraspecific studies based on δ 15 N values found a positive relationship between size and inferred trophic position. Here, we use datasets of predatory vertebrate ectotherms (crocodilians, turtles, lizards and fishes) to show that, although there are positive intraspecific relationships between size and δ 15 N values, relationships between stomach-content-based trophic level (TP diet ) and size are undetectable or negative. As there is usually no single value for 15 N trophic discrimination factor (TDF) applicable to a predator species or its prey, estimates of trophic position based on δ 15 N in ectotherm vertebrates with large size ranges, may be inaccurate and biased. We urge a reconsideration of the sole use of δ 15 N values to assess trophic position and encourage the combined use of isotopes and stomach contents to assess diet and trophic level.